The Implementation of Curriculum 2013 in English Teaching-Learning Process at SMA Negeri 1 Lubuk Pakam - Windasari Safitri Sinambela; Siti Aisah Ginting (LINGUISTIK TERAPAN, 2016)
This study deals with the implementation of Curriculum 2013 in English teaching learning process at SMA Negeri 1 Lubuk Pakam. The aims of this study were to describe the teachers’ effort in English teaching-learning process by applying scientific approach, to describe the teachers’ impelementation in English teaching-learning process by applying scientific approach, and to explain the teachers’ reasons to for the implement the scientific approach on that way. This study conducted by using qualitative research design. The source data of this study were teachers at XI IPA 1 and X IPS 1 SMA Negeri 1 Lubuk Pakam comprised two teachers. The data of this study was the implementation of Curriculum 2013 on teaching-learning English process in the classroom. The data was analyzed by using Interactive Model by Miles, Huberman, and Saldana. Based on data analysis, it was found that the teachers did not implement all the curriculum 2013 steps correctly,  the teachers’ reasons for the implement curriculum 2013 on their way because the teachers had many experience in teaching, curriculum 2013 was done only because of the rule from the school. Other reasons were because they had short time in teaching and lacked of the books for material in curriculum 2013.   Keywords: curriculum 2013, implementation, English teaching learning process, scientific approach